Bimbingan Pembuatan Alat Peraga Periskop Berbasis Lingkungan Dengan Penerapan Model E-STEM PjBL Pada Siswa - Muzana, Syarifah; Lubis, Silvi Puspa Widya; Rina Mirdayanti; Elin Lismayanti; Ramita (Rengganis Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to provide guidance to students in making environmentally based periscope teaching aids using the E-STEM PjBL model at SD Negeri 2 Klieng. This activity was carried out in three stages, namely the preparation stage, including coordinating the implementation with partners, which was carried out in June, the implementation stage, namely carrying out activities to make environmentally based periscope props, which were carried out by students and assisted by guidance by teachers and the Unaya TEAM, which was carried out in the month of June. September, the third stage of evaluation is to evaluate activities so as to obtain advantages and disadvantages which will be used as a reference for future activities carried out in September. The results obtained from this activity are project learning by making environmentally based periscope props which can increase students' creativity very well. The conclusion of this activity is that students are able to make environmentally based periscope props so that they can increase students' creativity when studying in class.